Analisis Penggunaan Model Game Based Learning Pada Materi Operasi Hitung Pecahan Di Sekolah Dasar Kelas V: Analysis of the Use of Game-Based Learning Models in Teaching Fraction Operations to Fifth-Grade Elementary School Students - Masah Masah; Maryam Maryam; Patra Aghtiar Rakhman (Sumule Indonesia Publishing, 2025)
The purpose of this study is to describe and analyze the use of the Game-Based Learning (GBL) learning model on fractional arithmetic operations in grade V elementary school. This study uses a literature review research type with the selected review model being a narrative review. This study was conducted through the stage of collecting library source data, namely by analyzing published journals. From the results of the study, it can be concluded that the use of the Game-Based Learning (GBL) model in mathematics learning, especially on fractional material, can have a positive effect on a pleasant learning atmosphere for students so that students can create a different learning experience from other learning models. Mathematics learning using the game-based learning model can create an interactive learning atmosphere because this learning model requires students to actively participate in the learning process as game players. The method used is qualitative, with data sources used in the form of secondary data obtained from several journals published in the last five years, articles, and previous research that have been analyzed by the author related to the problems to be studied in this study.